Pharmacokinetics, Safety, and 48-Week Efficacy of Oral Raltegravir in HIV-1–Infected Children Aged 2 Through 18 Years. (21st October 2013) - Nachman, Sharon; Zheng, Nan; Acosta, Edward P.; Teppler, Hedy; Homony, Brenda; Graham, Bobbie; Fenton, Terence; Xu, Xia; Wenning, Larissa; Spector, Stephen A.; Frenkel, Lisa M.; Alvero, Carmelita; et al.
Abstract : Novel, potent, and well-tolerated antiretroviral agents in appropriate formulations are acutely needed for HIV-infected pediatric patients of all ages. This study was designed to assess the safety and pharmacokinetics of raltegravir in HIV-infected children aged 4 weeks to <19 years. Abstract: Background.  IMPAACT P1066 is a phase I/II open-label multicenter trial to evaluate pharmacokinetics, safety, tolerability, and efficacy of multiple raltegravir formulations in human immunodeficiency virus (HIV)–infected youth. Methods.  Dose selection for each cohort (I: 12 to <19 years; II: 6 to <12 years; and III: 2 to <6 years) was based on review of short-term safety (4 weeks) and intensive pharmacokinetic evaluation. Safety data through weeks 24 and 48, and grade ≥3 or serious adverse events (AEs) were assessed. The primary virologic endpoint was achieving HIV RNA <400 copies/mL or ≥1 log10 reduction between baseline and week 24. Results.  The targeted pharmacokinetic parameters (AUC0-12h and C12h ) were achieved for each cohort, allowing dose selection for 2 formulations. Of 96 final dose subjects, there were 15 subjects with grade 3 or higher clinical AEs (1 subject with drug-related [DR] psychomotor hyperactivity and insomnia); 16 subjects with grade 3 or higher laboratory AEs (1 with DR transaminase elevation); 14 subjects with serious clinical AEs (1 with DR rash); and 1 subjects with serious laboratory AEs (1 with DR transaminase increased). There were no discontinuations due to AEs and no DR deaths. Favorable virologic responses at week 48 were observed in 79.1% of patients, with a mean CD4 increase of 156 cells/µL (4.6%). Conclusions.  Raltegravir as a film-coated tablet 400 mg twice daily (6 to <19 years, and ≥25 kg) and chewable tablet 6 mg/kg (maximum dose 300 mg) twice daily (2 to <12 years) was well tolerated and showed favorable virologic and immunologic responses. Clinical Trials Registration  NCT00485264.